Avaliação psicológica antecipatória em casos judiciais de alienação parental - Nikolic Meierhoefer, Jovane (2022)
Brazilian children and adolescents who are victims of this moral abuse end up being exposed to the hostile family environment for many years until multidisciplinary reports can suggest the most appropriate mechanisms for promoting the health of those individuals. The objectives of this master's thesis were to investigate the anticipatory psychological assessment and describe experiences of professionals who participate in the processes of Parental Alienation. A descriptive exploratory cross-sectional study was carried out. Data collection was carried out through a questionnaire (Google Forms) developed by the author, in Survey mode, in a virtual environment. The sample, for convenience, consisted of 143 professionals from different areas such as lawyers, psychologists, technical assistants, mediators, conciliators, judges and judges, whose professional routine involves this theme. The results showed that the protection of the child's or adolescent's biopsychosocial development suggests including the study of bonds with the alienated parent, through a multidisciplinary assessment carried out in the initial phase of the postulator period. Of the respondents to the questionnaire, 87.4% chose the option that the hypothesis of this study would reduce the temporal lapse of actions, thus anticipating the judicial protection. In this way, the relevance of reducing the time of exposure to the conflicting family environment is emphasized, a priority to be observed regarding the full protection of children or adolescents established as a fundamental right. (AU)